O ambiente virtual de aprendizagem moodle como apoio ao ensino presencial da disciplina matemática na educação de jovens e adultos - Fernandes, Rosane Rosa Dias (2013)
The objective of this work was to analyze the deployment process and collaborative learning environment using moodle to support face-to-face education in teachinglearning process of Mathematical discipline in adult and youth education. The research work was developed in a group of seven students of the Trading Technical Course of PROEJA at Ifes Campus of Colatina. Interactive exercises of the project Descartes from the Spanish Ministry of Education, Culture and Sports were used in the moodle for the content: "Orthogonal Cartesian system". The study analyzes the virtual-room- planning process to mathematical activities, identifies the students ' difficulties, the interaction between the participants, the viability of the virtual environment as a tool to support face-to-face teaching, as well as its influence on the process of teaching and learning of Mathematics. Through this movement, it seeks justification on theoretical assumptions of socio-historical theory of Vygostsky and in the studies of Paulo Freire. It dialogues with authors such as Moran, Lévy, Valente and Kenski, who subsidize discussions raised during of the study, and it also adopts concepts of Ethnomathematics of D ' Ambrosio. Oliveira and Fávero subsidize the EJA. The research uses the case-study methodology, favoring the participant observation. Along the work, interviews with the students, as well as with the Mathematics teacher and the pedagogue of the course were carried out. In addition, questionnaires were applied for data generation, and documentary research. Judging by the testimonies and the observations collected, the activities in the virtual environment pleased the students and brought out the concept of "doing math", with gains for the students learning of Mathematics. The use of moodle virtual environment seems to have helped in the development of the skills required